2008
DOI: 10.1002/cphc.200700857
|View full text |Cite
|
Sign up to set email alerts
|

(Thermo)dynamic Role of Receptor Flexibility, Entropy, and Motional Correlation in Protein–Ligand Binding

Abstract: The binding of 2-amino-5-methylthiazole to the W191G cavity mutant of cytochrome c peroxidase is an ideal test case to investigate the entropic contribution to the binding free energy due to changes in receptor flexibility. The dynamic and thermodynamic role of receptor flexibility are studied by 50 ns-long explicit-solvent molecular dynamics simulations of three separate receptor ensembles: W191G binding a K(+) ion, W191G-2a5mt complex with a closed 190-195 gating loop, and apo with an open loop. We employ a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 51 publications
5
51
0
1
Order By: Relevance
“…The conclusion that correlation contributes significantly to configurational entropy differences is consistent with a prior quasiharmonic study using Cartesian coordinates 7 and with MIE 23,24 studies using bond-angle-torsion coordinates. It is also consistent with a recent study that applied MIST to side-chain rotameric states across a series of different proteins.…”
Section: Discussionsupporting
confidence: 87%
“…The conclusion that correlation contributes significantly to configurational entropy differences is consistent with a prior quasiharmonic study using Cartesian coordinates 7 and with MIE 23,24 studies using bond-angle-torsion coordinates. It is also consistent with a recent study that applied MIST to side-chain rotameric states across a series of different proteins.…”
Section: Discussionsupporting
confidence: 87%
“…The extent of this induced conformational entropy has been shown to control the affinity [36]. These studies, among others [37][38][39][40], support the validity of ligand binding through entropic expansion for disordered proteins.…”
Section: Thermodynamics Of Protein-ligand Bindingmentioning
confidence: 70%
“…Such a behavior of two entropy estimation approaches used here is inline with the known fact that QH gives an upper bound of conformational entropy, while the entropy approximated just based on dihedral angles' distributions usually represents an underestimate of the real value. 18,53 First, we observed that both S conf -QH and S conf -dihedral are decreased by monomers as compared to the "pure" bilayer ( Figure S8, lower panels), and this effect has a reverse correspondence to the observed heterogeneity increase upon monomer inclusions ( Figure S8, upper panels). The change in both conformational entropies is also negative for all dimers as compared to the pure bilayer.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 73%